Idiopathic Thoracic Spontaneous Spinal Epidural Hematoma - Abdurrahman Aycan; Seymen Ozdemir; Harun Arslan; Edip Gonullu; Cemal Bozkına (Case Reports in Surgery)
A 33-year-old male patient experienced temporary sensory loss and weakness in the right lower extremity one month prior to admission. The patient was admitted to a private clinic with a three-day history of acute onset of sensory loss and weakness in both lower extremities and was treated and followed up with a prediagnosis of transverse myelitis and the Guillain-Barre syndrome (GBS). The patient was subsequently transferred to our clinic and the neurologic examination revealed paraplegia in both lower extremities, positive bilateral Babinski signs, and hypesthesia below the T10 dermatome with saddle anesthesia. The patient had urinary incontinence and thoracic magnetic resonance imaging (MRI) showed an image of a mass compressing the medulla.